Pulp Response to Clinical Procedures and Dental Materials - Hebling, Josimeri [UNESP]; Mendes-Soares, Igor Paulino [UNESP]; de Oliveira Ribeiro, Rafael Antonio [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer Nature, 2023)
This chapter aims to provide readers with reliable, evidence-based data obtained from laboratory studies and clinical trials performed in the last decades in different fields of dentistry related to dental materials, as well as pulp biology and regeneration. Several relevant pieces of information about the responses of the dentin-pulp complex against clinical procedures and many cytotoxic or bioactive dental products recommended to be applied on enamel, dentin, and exposed pulps were reported and critically discussed. Sequences of clinical applications of specific resin-based dental materials were included in this chapter, and histopathological micrographs of human teeth submitted to variable clinical procedures were also presented to make the relations between dental materials and the dentin-pulp complex clearer to the readers. Overall, the authors consider that within contemporary restorative dentistry, using minimally invasive operative techniques associated with applying dental materials that present scientifically proven properties to be safely employed in specific clinical situations must be routine for clinicians. This professional and responsible attitude will undoubtedly result in a greater chance of achieving clinical success, benefiting patients and dentists.
Keywords: Biocompatibility; Cytotoxicity; Dental materials; Dentin; Pulp